(untitled) (Research, Society and Development, 2021)
The rice is a cereal present in the daily Brazilian basic nutrition which, the demand grows as population increases. Upland rice is a kind of agricultural crop that it has gained space because it is able to use and to recover soils of areas while to ensure income to producers and it supply the demand for the grain. Therefore, technologies are necessary to increase the yield in upland rice, which are more sustainable and which can reduce the cost of production in agricultural areas. The objective of work was to evaluate the seed inoculation of rice with Azospirillum brasilense associated with doses of recommended nitrogen fertilization doses in sowing and topdressing (0, 50 e 100%). The experimental design was randomized blocks with four replications. The study was developed in the 2013/14 season in a typical dystrophic Red Latosol (Oxisol), in Selvíria - MS. The presence of 100% of the recommended N dose reduced the hectolitric mass of grains. The inoculation with A. brasilense + 50% of the recommended N dose and, absence of inoculation + 100% of the recommended N dose provided increase in the number of panicles m-2. The inoculation with A. brasilense associated or not to the fertilization with 50% of the recommended N dose fostered gains in yield of upland rice.